Developing a Local Culture-Based Character Design Module Using the ADDIE Model - Wardaya, Marina; Megawati , Shienny (IJORER : International Journal of Recent Educational Research, 2026)
The integration of local cultural values into visual design remains a challenge for many Indonesian creators, despite the growing global influence of comics, games, and animation. This gap highlights the need for structured educational resources that guide students in embedding cultural identity within contemporary visual narratives. The purpose of this study is to develop a local culture-based character design module that supports design education and creative industry practices. The method used in this study is the ADDIE instructional design model, which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. Data were collected through literature studies on cultural identity, visual semiotics, and mythology, complemented by in-depth interviews with local creators and design educators. The module was designed to balance aesthetic appeal with the representation of cultural values and symbolic meaning. The results of this study are a prototype module that integrates local cultural narratives and visual semiotic principles into character design processes. The prototype was validated through expert feedback and limited trials with design students, which demonstrated that the module is both pedagogically relevant and adaptable to diverse media contexts. The conclusion of this study is that the integration of cultural identity into design education through a structured module can enhance students’ creative sensitivity and cultural awareness, enabling them to create character designs that are not only visually appealing but also contextually meaningful and globally competitive.